Results of a clinical trial of humeral neck osteosynthesis with carbon - carbon composite material - M. L. Golovakha; V. V. Chornyi (Zaporozhye State Medical University, 2023)
The metals utilized in the production of various implants in traumatology possess all the required mechanical properties. However, these materials are susceptible to oxidation. Carbon-carbon composites, on the other hand, exhibit X-ray transparency and are easily machinable. Thanks to their intricate yet essential physical, mechanical, and chemical properties, they find effective application in osteosynthesis and endoprosthesis procedures for bone structures. The aim of this study is to comparative view of the treatment outcomes for patients with fractures of the proximal part of the humerus by carbon-carbon composite material plates and titanium plates. Materials and methods. In this study, a carbon-carbon composite material plate was conducted osteosynthesis of the proximal part of the shoulder. In the comparison group, a titanium plate was employed. The study group comprised 20 patients, while the comparison group included 15 patients. The analysis of the results was carried out utilizing the Constant-Murley scale and the Quick DASH questionnaire. Results. A comparative study of treatment outcomes between the main and comparison groups revealed a more significant positive treatment effect in the group that underwent osteosynthesis of the humeral neck by a carbon-carbon composite material plate. This effect was observed at the 3-month, 6-month, and 12-month evaluation points. It was characterized by reduced shoulder pain, alleviated dysfunction manifestations, enhanced daily activities, and improved overall quality of life among patients in this group. Conclusions. The analysis of long-term treatment outcomes for proximal humerus fractures, utilizing both carbon-carbon composite material plates and titanium plates, by the Constant-Murley scale and the Quick DASH questionnaire, demonstrated statistically confirmed improvements in shoulder joint function for both treatment methods.